MENINGKATKAN PENGETAHUAN REMAJA TERKAIT DAMPAK PERGAULAN BEBAS: MENINGKATKAN PENGETAHUAN REMAJA TERKAIT DAMPAK PERGAULAN BEBAS - Andri Kusuma Wijaya; Fatsiwi, Fatsiwi Nunik Andari; Nopia Wati (Gayaku Publisher, 2023)
Adolescents' knowledge about the consequences of promiscuity is the ability of adolescents to understand promiscuous sexual acts, which are sexual relations between men and women that occur in the absence of marriage or marriage. Free sexual activity that has occurred for some time has become one of the problems experienced by Indonesian teenagers. Adolescents in their social circles are very easily influenced by invitations from the opposite sex to carry out sexual deviant activities based on mutual liking and high curiosity. Adolescents never think about the impact of the sexual activities they engage in, starting from the negative impacts that society views that adolescents will receive as well as the health impacts that will occur with sexual relations outside of marriage. These teenagers usually still have the status of students or schoolgirls so they need to receive special attention in terms of improving cognitive abilities or knowledge about the impacts of free sexual activities which often occur in student or female students' environments. Providing inaccurate information will cause the student's perception or behavior to experience deviations, one of which is free sexual activity. If this condition is allowed to continue, it will increase free sexual behavior among teenagers, in this case students. There are several impacts of deviant behavior such as free sex which will result in unwanted pregnancies, having abortions as a result of free sex, experiencing health problems such as being at risk of being infected with HIV/AIDS. Forms of prevention that can be taken to minimize these various impacts require health education to be provided so that students can understand the consequences and impacts of promiscuity activities, especially free sex, so that it is hoped that promiscuous sexual behavior can be avoided and minimized by students as successors of the life of the nation and state